Poverty and its treatment in the jurisprudence of the Colombian constitutional court (1991-2015) (2018)
The present work aims to realize a quantitative and qualitative analysis of the social and legal phenomenon of poverty by the jurisprudence of the Colombian Constitutional Court with the finality of observe (i) the protection level recognized to people whose precarious social economic condition puts them in a special vulnerability situation, (ii) the aim and scope of the protected rights, (iii) the orders that had been proffered and (iv) the constitutional consequences that it implies in matter of judicialization of policies to fight against poverty. © 2018, Universidad de Talca. All rights reserved.